Managing Complex Investment Procedures: The Corporate Strategy to Address Uncertainty Construction Policies in Indonesia - Effnu Subiyanto (Master of Management, School of Business and Management, Petra Christian University, 2023)
This study aims to obtain notice, knowledge, and practical experience to help-guiding-investors on how to anticipate and deal with complicated investment procedures in Indonesia. As a developing country, Indonesia is well known for applying complicated and overlapped procedures. The complex procedures start in the beginning phase, during construction, and even arise again when the construction phase has nearly completed to enter operation. The methods presented are based on mixed interdisciplinary analyses. In preliminary, we enhanced the initial data using case studies. In the next phase, we validate through an exploratory study combined with an analytical hierarchy process. We provide an additional stage of descriptive analysis before we conclude as research findings. The results found that investors must first build a bolstered project team to address the complicated procedures. The team has addressed five stages that must be carefully handled: the preparation phase, procurement stage, groundbreaking and construction period, commissioning time, and the scheduled closing ceremonies. The most attention is addressing the preparation stage. Despite being proven in the cement projects, the findings can be implemented in other construction projects with several adjustments. This study demonstrated better building governance for societies and Nations and would be beneficial to improve the fairness climate for the Government of Indonesia.